STRATEGI BERTAHAN HIDUP PETANI PERKOTAAN DI KOTA GORONTALO - Syamsir Syamsir; Zainal Abidin; Irmawati Irmawati; Neisi Tri Andila Mamonto; Fadila Julianti Larekeng (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2024)
Gorontalo City is the capital city of Gorontalo Province; however, in some places in Gorontalo City, there are still scattered agricultural lands and most of the agricultural land is surrounded by buildings and housing. The purpose of this study was to determine the survival strategy of urban farmers in Gorontalo City and analyze income based on the cost of living for farmers and their families. Secondary data in this study were obtained from the Agricultural Extension Center (BPP) and the Badan Pusat Statistik (BPS) or relevant sources in the form of data on the number of farmers in Gorontalo City. This study uses a mixed-methods approach, namely quantitative and qualitative approaches. Primary data were obtained from interviews with research informants, with a limit on the number of informants to as many as 30 farmers. The primary data collection instrument was divided into two types: questionnaire A for all informants and questionnaire B for 10 informant farmers (with the criteria of separate land from other farmers' land) through the in-depth interview method. A qualitative approach with interactive analysis of the Miles and Huberman model. The results showed that the income of rice farmers was Rp. 489.586348 with 27 farmers, tomato commodities were Rp. 20.991.667 with 2 farmers, and mustard commodities were Rp. 5.160.000 with 1 farmer. The total family living cost of the respondents per month is Rp. 87,799,980. In general, farmers use a double-income strategy to meet the needs of their families, such as pulling bentor (ngojek), workshops, and construction workers